2016
DOI: 10.1136/annrheumdis-2016-210297
|View full text |Cite
|
Sign up to set email alerts
|

Low immunogenicity of tocilizumab in patients with rheumatoid arthritis

Abstract: ObjectiveSubcutaneous (SC) and intravenous formulations of tocilizumab (TCZ) are available for the treatment of patients with rheumatoid arthritis (RA), based on the efficacy and safety observed in clinical trials. Anti-TCZ antibody development and its impact on safety and efficacy were evaluated in adult patients with RA treated with intravenous TCZ (TCZ-IV) or TCZ-SC as monotherapy or in combination with conventional synthetic disease-modifying antirheumatic drugs (csDMARDs).MethodsData from 5 TCZ-SC and 8 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 39 publications
5
71
1
2
Order By: Relevance
“…Only nine patients tested positive for neutralising anti-TCZ antibodies, none of whom withdrew because of insufficient therapeutic response or loss of efficacy, consistent with previous reports. 13 Because of the complexity of multiple comparisons, all week 104 analyses were exploratory, which is a limitation of this study. Post-week 52 data for the 4 mg/kg TCZ+MTX and placebo+MTX groups should be interpreted with caution given the large number of patients switching to escape therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Only nine patients tested positive for neutralising anti-TCZ antibodies, none of whom withdrew because of insufficient therapeutic response or loss of efficacy, consistent with previous reports. 13 Because of the complexity of multiple comparisons, all week 104 analyses were exploratory, which is a limitation of this study. Post-week 52 data for the 4 mg/kg TCZ+MTX and placebo+MTX groups should be interpreted with caution given the large number of patients switching to escape therapy.…”
Section: Discussionmentioning
confidence: 99%
“…One safety concern of biologic therapies is the development of anti-drug antibodies, which can lead to loss of efficacy and/or immune-mediated adverse reactions 174 . A study evaluating the immunogenicity of tocilizumab in patients with RA found that the incidence of antibodies to tocilizumab was low, regardless of the route of administration of tocilizumab or whether it was used as monotherapy or in combination with csDMARDs; moreover, antibodies to tocilizumab were mostly transient, and their development did not correlate with pharmacokinetics, safety events or loss of efficacy 174 .…”
Section: Safety Of Il-6 Inhibitionmentioning
confidence: 99%
“…The PK profile [28,29,31]. In a pooled analysis of data from 13 phase 3 clinical trials (8 TCZ-IV, 5 TCZ-SC) and one TCZ-IV safety study, antidrug antibodies were identified in 47 of 3094 (1.5%) and 69 of 5806 (1.2%) patients treated with TCZ-SC and TCZ-IV, respectively [76]; neutralizing antidrug antibodies were confirmed in 40 of 3094 (1.3%) and 54 of 5806 (0.9%) of these patients, respectively [76].In summary, the safety, PK, and immunogenicity of TCZ-SC appear to be similar to those for TCZ-IV. …”
mentioning
confidence: 99%